2018
DOI: 10.1590/1676-0611-bn-2017-0394
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Holocene marine fish of the southeast coast of Brazil

Abstract: Middens are archaeological sites dating between 8,000 and 1,000 years before present and are commonly found on the Brazilian coast. Data were collected from 68 middens allowing an inventory of 142 fish species, most of them recorded in no more than five sites. Conversely, Micropogonias furnieri and Pogonias cromis had the highest frequencies of occurrence. The biogeographic, ecological and economic data showed that most of the identified fish are widely distributed in the Western Atlantic (59.72%) and inhabit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Furthermore, Souza et al (2010a) showed that single malacological inventories for large areas such as São Paulo Coast (Arruda et al, 2003) and Southeast Brazilian Coast (Denadai et al, 2001) were able to sample as little as 6.5% and 3.4% respectively of the total number of species for these areas. Comparing with other taxa found in sambaquis, Mendes et al (2018) showed that only 17.6% of all fish species found in the coast of Rio de Janeiro were found in an inventory of all sambaquis for the same region. Therefore, 30% is by no means a negligible number of species on such circumstances.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, Souza et al (2010a) showed that single malacological inventories for large areas such as São Paulo Coast (Arruda et al, 2003) and Southeast Brazilian Coast (Denadai et al, 2001) were able to sample as little as 6.5% and 3.4% respectively of the total number of species for these areas. Comparing with other taxa found in sambaquis, Mendes et al (2018) showed that only 17.6% of all fish species found in the coast of Rio de Janeiro were found in an inventory of all sambaquis for the same region. Therefore, 30% is by no means a negligible number of species on such circumstances.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, shell mounds are also repository of information on living fauna existing during the late Holocene. Based on that, some recent studies have been using shell mounds to describe the fauna composition of the Holocene, especially mollusks and fishes (Souza et al, 2010a(Souza et al, , 2012(Souza et al, , 2016Mendes et al, 2014Mendes et al, , 2018Beauclair et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Zooarchaeological remains have been used to assess the past biodiversity, to understand the ecological changes in a given ecosystem, and have shown that marine fauna species may have been much more abundant and diverse than is currently perceived (Jackson et al ., 2001; Pinnegar & Engelhard, 2008). The use of zooarchaeological remains has increased in recent years as a source of information about historical biodiversity ( e.g ., Lopes et al ., 2016; Mendes et al ., 2018). Despite the limitations of zooarchaeological data ( e.g ., human bias as selective fisheries), studies show it can be used to assess marine Holocene biodiversity, as these are not statistically different from current biodiversity inventories (Mendes et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Shark remains such as teeth and vertebrae are ubiquitous in archaeological sites on the south and south‐east Brazilian coast. More recent studies identifying the biodiversity of marine fauna present in archaeological sites have been carried out in Brazil's south‐eastern region ( e.g ., Lopes et al ., 2016; Mendes et al ., 2018). These studies show incredible biodiversity of fish assemblages, evidencing well‐developed fisheries and the historical potential for the exploitation and overexploitation of fish populations and possible nurseries areas.…”
Section: Introductionmentioning
confidence: 99%
“…In most surveys of fish populations on the Brazilian coast, however, E. saurus has been identified as the most common elopid species (Franco et al 2014, garcia-Junior et al 2015, Pinheiro et al 2015, Marceniuk et al 2017, Medeiros et al 2018, Mendes et al 2018.…”
Section: Introductionmentioning
confidence: 99%